A Review of Protist Grazing Below the Photic Zone Emphasizing Studies of Oxygen-Depleted Water Columns and Recent Applications of In situ Approaches - Medina, Luis E.; Taylor, Craig D.; Pachiadaki, Maria G.; Henríquez-Castillo, Carlos; Ulloa, Osvaldo; Edgcomb, Virginia P. (Frontiers in Marine Science, 2017)
Little is still known of the impacts of protist grazing on bacterioplankton communities in the dark ocean. Furthermore, the accuracy of assessments of in situ microbial activities, including protist grazing, can be affected by sampling artifacts introduced during sample retrieval and downstream manipulations. Potential artifacts may be increased when working with deep-sea samples or samples from chemically unique water columns such as oxygen minimum zones (OMZs). OMZs are oxygen-depleted regions in the ocean, where oxygen concentrations can drop to <20 μM. These regions are typically located near eastern boundary upwelling systems and currently occur in waters occupying below about 8% of total ocean surface area, representing ~1% of the ocean's volume. OMZs have a profound impact not only on the distribution of marine Metazoa, but also on the composition and activities of microbial communities at the base of marine food webs. Here we present an overview of current knowledge of protist phagotrophy below the photic zone, emphasizing studies of oxygen-depleted waters and presenting results of the first attempt to implement new technology for conducting these incubation studies completely in situ (the Microbial Sampling- Submersible Incubation Device, MS-SID). We performed 24-h incubation experiments in the Eastern Tropical South Pacific (ETSP) OMZ. This preliminary study shows that up to 28% of bacterial biomass may be consumed by protists in waters where oxygen concentrations were down to ~4.8 μM and up to 13% at a station with nitrite accumulation where oxygen concentrations were undetectable. Results also show that shipboard measurements of grazing rates were lower than rates measured from the same water using the MS-SID, suggesting that in situ experiments help to minimize artifacts that may be introduced when conducting incubation studies using waters collected from below the photic zone, particularly from oxygen-depleted regions of the water column.